2021
DOI: 10.1186/s13023-021-01749-w
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of up to 15 years effects of lipoprotein apheresis on lipids, biomarkers of inflammation, and soluble endoglin in familial hypercholesterolemia patients

Abstract: Background Lipoprotein apheresis (LA) is considered as an add-on therapy for patients with familial hypercholesterolemia (FH). We aimed to analyze the data collected in the last 15 years from FH patients treated with LA, to elucidate the benefit of this procedure with respect to plasma lipids, biomarkers of inflammation, and endothelial dysfunction and soluble endoglin. Results 14 patients (10 heterozygous FH patients (HeFH), 4 homozygous FH patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…J. Višek et al . [ 42 ] analyzed data on FH patients treated with LA for 15 years. They found that long-term LA treatment improved lipid levels and endothelial dysfunction, without cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…J. Višek et al . [ 42 ] analyzed data on FH patients treated with LA for 15 years. They found that long-term LA treatment improved lipid levels and endothelial dysfunction, without cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pathogenic role of sEng in preeclampsia-associated hypertension and renal involvement has been demonstrated in several in vivo studies [9,[18][19][20]. Abnormal high levels of sEng are also found in other cardiovascular-related conditions such as atherosclerosis, hypercholesterolemia [21,22], diabetes mellitus [23][24][25], diabetic retinopathy [26], hypertension [23], circulatory failure in septic shock syndrome [27], coronary artery disease [28][29][30], acute myocardial infarction [31], and reperfusion after cerebral large-vessel occlusion [32]. These findings are in agreement with several in vivo and in vitro studies supporting an active role of sEng in endothelial dysfunction and vascular remodeling [33][34][35].…”
Section: Introductionmentioning
confidence: 93%
“…3, 4 LA has to be repeated weekly or biweekly, as LDL-C levels increase after each session. 3, 5 Although the lipid-lowering effect of LA is strong, its impact on preventing ASCVD in HoFH is difficult to analyse. HoFH is rare, LA is not available for many patients around the globe and if available, it is not ethical to withhold children from LA to analyse the clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%